Pendampingan Edukasi Sadar Hukum Bahaya Narkoba dan Judi Online Bagi Pelajar SMAN 1 Pamarayan - Alhaetami, Mochamad Basit; Sari, Putri; Rasidi, Rasidi; Aritonang, Tiur Maulina; Yanti, Novi (Annusfy : Journal of Multidisciplinary Research, 2025)
This community service activity aims to increase students' knowledge, legal awareness, and critical thinking skills so they can avoid deviant behavior regarding the dangers of drugs and online gambling. It was implemented through interactive lectures, discussions, educational media screenings, and a question-and-answer session. The mentoring activity demonstrated a positive response from participants, not only understanding the health dangers of drugs but also recognizing the strict legal implications. Similarly, regarding online gambling, students understood that this activity is a criminal offense that can lead to financial loss and addiction.